2015
DOI: 10.1039/c5nr01651g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phase-pure and monodisperse iron oxide nanoparticles by thermal decomposition

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) are used for a wide range of biomedical applications requiring precise control over their physical and magnetic properties, which are dependent on their size and crystallographic phase. Here we present a comprehensive template for the design and synthesis of iron oxide nanoparticles with control over size, size distribution, phase, and resulting magnetic properties. We investigate critical parameters for synthesis of monodisperse SPIONs by organic thermal dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(201 citation statements)
references
References 73 publications
(147 reference statements)
5
192
1
3
Order By: Relevance
“…First, the effect of discharge power was investigated, when the plasma power was varied from 1.3 to 3.4 W while keeping a constant precursor concentration (35 ppm, condition 1-4). Next, the influence of precursor concentration was studied by operating the plasmas in the same power range but with half the precursor concentrations (17.5 ppm, condition [5][6][7][8]. The typical procedure was as follows: a discharge was ignited in pure argon.…”
Section: Experimental Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…First, the effect of discharge power was investigated, when the plasma power was varied from 1.3 to 3.4 W while keeping a constant precursor concentration (35 ppm, condition 1-4). Next, the influence of precursor concentration was studied by operating the plasmas in the same power range but with half the precursor concentrations (17.5 ppm, condition [5][6][7][8]. The typical procedure was as follows: a discharge was ignited in pure argon.…”
Section: Experimental Synthesismentioning
confidence: 99%
“…6 Iron oxide nanoparticles of maghemite structure (c-Fe 2 O 3 ) show excellent superparamagnetic behavior, in contrast to the antiferromagnetic nature of hematite (a-Fe 2 O 3 ). 7 Also, the hyperthermia therapy efficacy of Ni nanoparticles is affected by several parameters: (1) Composition. The existence of impurities will significantly reduce their magnetic performance.…”
Section: Introductionmentioning
confidence: 99%
“…MNP-5 exhibits a broader size distribution due to variances in the synthesis. As demonstrated by Hufschmid et al [29] adding oleic acid or reducing iron concentration broadens the size distribution. Since the mean size is close to MNP-6 it was interesting to investigate in which way a broader dispersity influences the heating slope of the materials.…”
Section: Resultsmentioning
confidence: 82%
“…[130] Actually, this non-hydrolytic method has been devoted to the fabrication of uniform MNPs by inspiration from semiconductor nanocrystals and oxide formation in non-aqueous media. [46a,131] As its name implies, it involves breaking down of materials to form new compositions at various temperatures.…”
Section: Thermal Decompositionmentioning
confidence: 99%
“…[145] In a recent study, Hufschmid et al evaluated and compared synthesis of iron oxide nanoparticles from decomposition of different precursors for their capability to produce iron oxide nanoparticles with specific size and phase-purity requirements. [130] It was www.advancedsciencenews.com www.advhealthmat.de concluded that pentacarbonyl synthesis is suited for synthesis of small (<10 nm) SPIONs, while both iron oleate and oxyhydroxide surpass the thermal decomposition method for production of larger (10-30 nm) particles. Particle size plays an important role on the blocking temperature of nanomagnets, thus a narrow size distribution of magnetic particles prevents polydispersion in a resulted sample.…”
Section: Thermal Decompositionmentioning
confidence: 99%